Direct oral anticoagulant plasma levels and thrombin generation on ST Genesia system. Issue 4 (23rd April 2020) - Pfrepper, Christian; Metze, Michael; Siegemund, Annelie; Klöter, Tristan; Siegemund, Thomas; Petros, Sirak
Abstract: Background: Monitoring of anticoagulant activity of direct oral anticoagulants (DOACs) can be necessary in special situations. DOAC plasma levels have a high inter‐ and intraindividual variation and do not necessarily reflect the coagulation status of the patient. Thrombin generation (TG) is a global hemostatic assay with the capacity to overcome this limitation. The aim of this study was to show correlations between DOAC plasma levels and TG parameters using the fully automated ST Genesia system. Methods: A total of 380 blood samples (120 with apixaban, 79 with dabigatran, 79 with edoxaban, and 102 with rivaroxaban) from patients at different time points after DOAC intake were included in the analysis. DOAC plasma levels were analyzed using calibrated anti‐Xa or anti‐IIa tests. Thrombin generation was measured using the ST Genesia system and STG‐DrugScreen reagent. Results: There was a significant correlation between the drug levels of all DOACs and the TG parameters' lag time and time to peak. Peak thrombin and velocity index show a negative correlation following an exponential regression curve with all anti‐Xa DOACs but not with dabigatran. Apart from a weak correlation with rivaroxaban, there was no correlation between drug levels of all other DOACs and endogenous thrombin potential. Conclusion: TG parameters measured with ST Genesia correlate with the drug levels of anti‐Xa DOACs. Peak thrombin and velocity index are of special interest for the determination of residual anticoagulant effect at low drug levels. For dabigatran‐treated patients, only lag time shows a correlation with the dabigatran plasma levels.